Temporal behavior of wheat – Puccinia striiformis interaction prompted defense-responsive genes. Issue 1 (31st December 2022) - Lata, Charu; Prasad, Pramod; Gangwar, O. P.; Adhikari, Sneha; Thakur, Rajni Kant; Savadi, Siddanna; Kumar, Kuldeep; Kumar, Subodh; Singh, G. P.; Bhardwaj, S. C.
ABSTRACT: Wheat stripe rust caused by Puccinia striiformis Westend. f.sp. tritici ( Pst ) is a global threat to wheat production. Genetic modification of defense-responsive factors in wheat rust interactions could help devise strategies to control stripe rust on wheat. This experiment studied the interaction between Pst pathotype 78S84 in PBW343 and FLW-3 by evaluating the quantitative temporal transcription profiles of defense-related genes at different time points. This is the first attempt to exhibit inter-connections among different proteins and depict a hypothetical model for the mechanism of R gene-mediated resistance. Transcript levels of LTP, AQP1, PR1, PR2, PR4, and PR10 were relatively higher under compatible interaction, while under incompatible interaction, transcript levels of COMT1, PRA2, WCAB, and PR9 were significantly high. This study projected the role of defense-responsive genes, inter-networking of proteins, and R gene-mediated resistance between wheat and stripe rust.